Leafy Vegetables Free Of Coliforms And Parasites After Washing In Chlorine Treated Water - Camila Luchesi; Bibiana Paula Dambrós; Jane Mary Lafayette Neves Gelinski; Monica Frighetto; César Milton Baratto (São Paulo State University (UNESP), 2016)
The production and preparation of vegetables for consumption involve procedures that pose health risks to consumers. In this context the water plays an important role in the quality of minimally processed vegetables. We assessed the hygienic-sanitary quality of leafy vegetables and obtained data of interest to health surveillance agencies and public health. They were tested for the presence of total and faecal coliforms, and also parasitic protozoa and helminths. The vegetable samples were purchased in supermarkets of the Midwest of the State of Santa Catarina, Brazil. We performed bacteriological analyses of wash water samples using chromogenic substrates to obtain the most probable number of the coliform group at 35 °C and Escherichia coli. We used Hoffman's spontaneous sedimentation technique for the parasitological analysis in order to check the occurrence of heavy and light helminths eggs and protozoan cysts. The analyses indicated the presence of coliforms, nematodes and freeliving protozoa, except for the last wash. We concluded that the washing process using running water and no active chlorine was not efficient in reducing the load of microorganisms in the vegetables. Therefore, intensive educational programmes should be implemented by health authorities to encourage hygienic-sanitary practices and risk reduction of food-borne diseases.